The Effect of Democratic Leadership, Motivation and Compensation on Employee Job Satisfaction: Pengaruh Kepemimpinan Demokratis, Motivasi dan Kompensasi terhadap Kepuasan Kerja Karyawan - Atmaja, Mahendra Dwi; Prapanca, Detak (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of democratic leadership, motivation, and compensation on employee job satisfaction at CV. Bina Teknik Sidoarjo. The method used in this research is a quantitative approach. Sampling in this study was carried out by saturated sampling method, with the number of respondents as many as 56 respondents, employees of CV. Bina Teknik Sidoarjo. The data analysis technique used in this study used the SPSS version 25 program. The results of this study prove that Democratic Leadership has a partial effect on job satisfaction of employees of CV. Bina Teknik Sidoarjo, Motivation has a partially insignificant effect on Job Satisfaction of employees of CV. Bina Teknik Sidoarjo, Compensation partially significant effect on job satisfaction of employees CV. Bina Teknik Sidoarjo, and Democratic Leadership, Motivation, compensation have a simultaneous effect on Employee Job Satisfaction CV. Bina Teknik Sidoarjo.